Muscle strength and regional lean body mass influence on mineral bone health in young male adults - Guimarães, Bianca Rosa (2018)
The relationship between muscle strength and bone mineral content (BMC) and bone mineral density (BMD) is supposed from the assumption of the mechanical stress influence on bone tissue metabolism. However, the direct relationship is not well established in younger men, since the enhancement of force able to produce effective changes in bone health, still needs to be further studied. This study aimed to analyze the influence of muscle strength on BMC and BMD in undergraduate students. Thirty six men (24.9 ± 8.6 y/o) were evaluated for regional and whole-body composition by dual energy X-ray absorptiometry (DXA). One repetition maximum tests (1RM) were assessed on flat bench-press (BP), lat-pull down (LPD), leg-curl (LC), knee extension (KE), and leg-press 45 (LP45) exercises. Linear regression modelled the relationships of BMD and BMC to the regional body composition and 1RM values. Measurements of dispersion and error (R2 adj and standard error of estimate (SEE)) were tested, setting at 0.05. The BMD mean value for whole-body was 1.12±0.09 g/cm2 and BMC attained 2477.9 ± 379.2 g. The regional lean mass (LM) in upper-limbs (UL) (= 6.80±1.21 kg) was related to BMC and BMD for UL (R2 adj = 0.74, p<0.01, SEE = 31.0 g and R2 adj = 0.63, SEE = 0.08 g/cm2), and LM in lower-limbs (LL) (= 19.13±2.50 kg) related to BMC and BMD for LL (R2 adj = 0.68, p<0,01, SEE = 99.3 g and R2 adj = 0.50, SEE = 0.20 g/cm2). The 1RM in BP was related to BMD (R2 adj = 0.51, SEE = 0.09 g/cm2), which was the strongest relationship among values of 1RM for men; but, 1RM on LPD was related to BMC (R2 adj = 0.47, p<0.01, SEE = 44.6 g), and LC was related to both BMC (R2 adj = 0.36, p<0.01, SEE = 142.0 g) and BMD (R2 adj = 0.29, p<0.01, SEE = 0.23 g/cm2). Hence, 1RM for multi-joint exercises is relevant to BMC and BMD in young men, strengthening the relationship between force and LM, and suggesting both to parametrizes bone mineral health.